Acceptability of real-time video counselling compared to other behavioural interventions for smoking cessation in rural and remote areas. (1st December 2020) - Byaruhanga, Judith; Wiggers, John; Paul, Christine L; Byrnes, Emma; Mitchell, Aimee; Lecathelinais, Christophe; Tzelepis, Flora
Highlights: 93.5 % of respondents felt video counselling for smoking cessation was acceptable. 90 % of respondents would recommend video support for quitting to friends or family. On 7 of 10 measures video counselling was as acceptable as telephone counselling. On all 7 measures video counselling was more acceptable than written materials. Quitlines could consider video counselling as another way to assist people to quit. Abstract: Background: This study evaluated the acceptability of real-time video counselling compared to a) telephone counselling and b) written materials in assisting rural and remote residents to quit smoking. Methods: Participants were recruited into a three-arm, parallel group randomised trial and randomly allocated to either: a) real-time video counselling; b) telephone counselling; or c) written materials. At 4-months post-baseline participants completed an online survey that examined self-reported acceptability and helpfulness of the support. Results: Overall, 93.5 % of video counselling participants and 96.2 % of telephone counselling participants who received support thought it was acceptable for a smoking cessation advisor to contact them via video software or telephone respectively. There were significant differences between video counselling and telephone counselling groups on three of 10 acceptability or helpfulness measures. Video counselling participants had significantly lower odds of reporting the number of calls were about right (OR 0.50, 95 % CI 0.27−0.93), recommending the support to family and friends (OR 0.18, 95 % CI 0.04−0.85) and reporting the support helped with motivation to try quitting (OR 0.24, 95 % CI 0.07−0.76) compared to telephone counselling participants. Video counselling participants had significantly greater odds than written materials participants of rating the support favourably on all seven acceptability and helpfulness items compared. Conclusions: Real-time video counselling for smoking cessation is acceptable and well-received by those living in rural and remote locations. Further research is required to enhance the three attributes that were less acceptable for video counselling than telephone counselling.